A formação do leitor literário: um estudo de caso com leitores de Harry Potter - Luiza Tropia Silva (2013)
This research focuses on discussing the Harry Potter series in relation to literary reading and the formation of readers, as well as the impact of those books in the reading habits of children and young people. This project has attempted to problematize the understanding of that which is currently named 'infantojuvenil' literature through the analyses of questionnaires and interviews conducted with teenagers and children that took part in a meeting about Harry Potter organized by a public library in Belo Horizonte, Brazil. The main objectives of the research methods - questionnaires and interviews - was to understand the reading practice of the these readers, particularly to investigate the effects of reading the Harry Potter series, considered a best seller, in their formation from a wider perspective. Some of the original questions were: How did those readers come across the series' books? Which factors have influenced the choice to read the series? What are their literary preferences? How do these readers take ownership of their own reading habits? How do those readers relate to the literary reading practices promoted by their schools? Another source for the project has been the data retrieved about the book lending statistics in the library where the group meets, spanning a period of time from 2004, the year in which the library system has been digitized, to 2012. By carrying out this survey, it has been possible to analyze the Harry Potter books lending data during this period and the number of books available for loan, to compare the amount of loans of Harry Potter books with other series, to confirm the interest and lack of interest in the books, as well as verify which other books and series have been lent frequently in the library. Drawing from all of those sources, the project discusses to which extend the Harry Potter books have influenced the literary formation of those readers. The research has concluded that the Harry Potter books represent a milestone in the lives of the surveyed readers, in some cases crucial to their literary formation. Furthermore, the series has been the first longer piece of literature that some of those readers have engaged with, contributing to the broadening and development of their reading practices.